2006
DOI: 10.1002/rcm.2738
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for proteolytic labeling–optimization of 18O incorporation and prohibition of back‐exchange

Abstract: Proteolytic (18)O labeling is a very powerful tool for differential analysis applied to proteome studies. However, it is a relatively new technique and the optimization of the labeling process still needs some attention. We found that the two-step post-proteolytic labeling should be favored over the conventional digestion of proteins in H(2) (18)O, since the former allows for higher sample concentrations and thus more favorable kinetics. It was demonstrated that the inhibitory effect of urea on (18)O incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
85
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 26 publications
4
85
1
Order By: Relevance
“…Subsequently, Hajkova et al [19] showed that the incorporation of the second 18 O atom can be substantially accelerated if the post-digestion 18 O labeling is carried out at a pH in the range of 5-6, depending on the enzyme used in this step. Storms et al [20] observed that prohibition of 18 O back-exchange can be efficiently accomplished by heating differentially labeled samples at 80 C for 10 min before combining them for subsequent MS analysis. Sevinsky et al [21] proposed the use of immobilized trypsin for both the proteolysis and the labeling step to provide protection for the isotopic tags throughout the IPG-IEF process and prevent the 18 O back-exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Hajkova et al [19] showed that the incorporation of the second 18 O atom can be substantially accelerated if the post-digestion 18 O labeling is carried out at a pH in the range of 5-6, depending on the enzyme used in this step. Storms et al [20] observed that prohibition of 18 O back-exchange can be efficiently accomplished by heating differentially labeled samples at 80 C for 10 min before combining them for subsequent MS analysis. Sevinsky et al [21] proposed the use of immobilized trypsin for both the proteolysis and the labeling step to provide protection for the isotopic tags throughout the IPG-IEF process and prevent the 18 O back-exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches aiming at preventing the ampholytes from entering the ion source have been developed. A microdialysis system at the ESI junction may allow the removal of the ampholytes out of the CE effluent leading to interference-free detection of proteins [29][30][31][32], but this complicated system has not gained wide acceptance. The online combination of CIEF and RPLC with ESI-MS detection is another option to circumvent ampholyte-related detection problems [26,[33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the relative abundance of each sample is calculated based on the relative intensities of the 'light' and 'heavy' labeled peptides provided by the mass spectrum. [14] The labeling reaction occurs during the hydrolysis of the peptide bond and, depending on the enzyme and on the reaction conditions, one or two 18 O-atoms from the H 18 2 O-enriched medium are incorporated at the C-terminal carboxyl group of the peptide. [9] Trypsin can catalyze the incorporation of two 18 O-atoms, resulting in the ideal mass shift of þ4 Da for the labeled peptide fragment, which is the minimum mass gap required to avoid naturally occurring isotopic interferences (e.g.…”
mentioning
confidence: 99%
“…[2][3][4][5] There are several SIL methodologies, e.g. : stable isotope labeling by amino acids in cell culture (SILAC), [6] isotope-coded affinity tags (ICAT), [7] and isobaric tag for relative and absolute quantitation (iTRAQ), [8] but the 18 O-enzymatic labeling of proteins is one of the most commonly used methods because it is a relatively cheap technique, easy to perform and versatile. [9][10][11][12][13] In the normal 18 O-labeling workflow one sample is labeled in 18 O-enriched water while the other is labeled in natural abundance 16 O water.…”
mentioning
confidence: 99%